Recognition of tumor cells by Dectin-1 orchestrates innate immune cells for anti-tumor responses - Chiba, Shiho; Ikushima, Hiroaki; Ueki, Hiroshi; Yanai, Hideyuki; Kimura, Yoshitaka; Hangai, Sho; Nishio, Junko; Negishi, Hideo; Tamura, Tomohiko; Saijo, Shinobu; Iwakura, Yoichiro; Taniguchi, Tadatsugu (eLife, 2014)
The eradication of tumor cells requires communication to and signaling by cells of the immune system. Natural killer (NK) cells are essential tumor-killing effector cells of the innate immune system; however, little is known about whether or how other immune cells recognize tumor cells to assist NK cells. Here, we show that the innate immune receptor Dectin-1 expressed on dendritic cells and macrophages is critical to NK-mediated killing of tumor cells that express N-glycan structures at high levels. Receptor recognition of these tumor cells causes the activation of the IRF5 transcription factor and downstream gene induction for the full-blown tumoricidal activity of NK cells. Consistent with this, we show exacerbated in vivo tumor growth in mice genetically deficient in either Dectin-1 or IRF5. The critical contribution of Dectin-1 in the recognition of and signaling by tumor cells may offer new insight into the anti-tumor immune system with therapeutic implications. When cells in the body grow and divide uncontrollably, cancerous tumors can form. An individual's likelihood of recovering from cancer is highly variable and often depends on the type of cancer and the extent of the disease at the start of treatment. Researchers are therefore interested in discovering how the body responds against cancerous cells. The first line of defense against infection and disease is the body's innate immune system, which includes a suite of immune cells known as white blood cells. These cells patrol the body's organs and tissues in an effort to immediately respond to pathogens and damaged, stressed or otherwise abnormal host cells. Among white blood cells, natural killer cells are involved in identifying and destroying tumor cells. However, it was unclear whether or how other immune cells might help natural killer cells to destroy tumors. In addition, although immune cells detect pathogens and injured cells by producing proteins called pattern recognition receptors, it was unknown whether these receptors also detect tumor cells. Here, Chiba et al. reveal that two other types of immune cell—dendritic cells and macrophages—play essential roles in helping natural killer cells to prevent tumors from growing in mice. The dendritic cells and macrophages produce a pattern recognition receptor called Dectin-1 that recognizes a molecule found on the surface of some—but not all—types of tumor cell. In doing so, Dectin-1 activates a critical signaling pathway and directs the activity of the natural killer cells so that they can effectively kill tumor cells. Chiba et al. found that these tumors grew faster in mice that lack the Dectin-1 protein. The findings of Chiba et al. may also help to explain the effectiveness of certain antibodies—proteins that recognize and neutralize foreign objects such as bacteria and viruses—in cancer therapy. In addition, the Dectin-1 pathway presents a new avenue of research that may offer new cancer treatments.